Women "in motion": the kinaesthetic viewing experience in Chinese viral advertising films. Issue 5 (2nd September 2020) - Biehl, Brigitte
ABSTRACT: Visual imagery provides aesthetic experiences for viewers, and viral advertising films address viewers' experience of movement which has not been analysed. Developing visual analyses, this study uses phenomenological approaches and the concept of kinaesthetic empathy, defined as the ability of viewers to react to movements, also in film. It considers Chinese Wei movies ("microfilms" or viral advertising films) with reference to examples by Audi and Swarovski as representatives of China's post-socialist marketing culture. Women in these films are presented as "in motion, " yet still are often delimited by traditional gender stereotypes. These films are potentially ambivalent ideological carriers that encourage women to reinvent themselves through consumption within traditional gender roles but may also suggest the pursuit of different experiences as movement is abstract, transitory and cannot be commodified.